2014
DOI: 10.1037/a0035738
|View full text |Cite
|
Sign up to set email alerts
|

Economic pressure, cultural adaptation stress, and marital quality among Mexican-origin couples.

Abstract: Based on data from a sample of 120 first-generation Mexican immigrant couples collected at the start of the Great Recession in the United States, this study tested an actor-partner interdependence mediation model (APIMeM) in which spouses' perceptions of stress related to economic pressure and cultural adaptation were linked to their own and their partners' reports of marital satisfaction through spouses' depressive symptoms and marital negativity. As hypothesized, results supported indirect links between econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
1
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 49 publications
4
64
1
6
Order By: Relevance
“…Thus, one pathway through which living in Chinese American families with a higher estimated per capita income might be associated with children's increased risk for behavioral problems is children's greater exposure to marital conflict. This result could not support the family stress model and is inconsistent with most previous studies, but similar to those obtained in studies conducted among economically disadvantage samples (e.g., Helms et al 2014;Robila and Krishnakumar 2005). In fact, that lower income immigrants are most likely to show a tendency toward nondisruption (Bean et al 1994;Sorensen and Enchautegui 1994), which suggests that the pattern is not entirely a cultural phenomenon, but rather a family adaptation strategy adopted to cope with economic and other immigrant related pressures.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Thus, one pathway through which living in Chinese American families with a higher estimated per capita income might be associated with children's increased risk for behavioral problems is children's greater exposure to marital conflict. This result could not support the family stress model and is inconsistent with most previous studies, but similar to those obtained in studies conducted among economically disadvantage samples (e.g., Helms et al 2014;Robila and Krishnakumar 2005). In fact, that lower income immigrants are most likely to show a tendency toward nondisruption (Bean et al 1994;Sorensen and Enchautegui 1994), which suggests that the pattern is not entirely a cultural phenomenon, but rather a family adaptation strategy adopted to cope with economic and other immigrant related pressures.…”
Section: Discussioncontrasting
confidence: 58%
“…In addition, lots of studies have suggested that economic stress was associated with marital conflict. Studies have shown that couples under economic pressure often interact with each other in destructive ways that lead to increased domestic problems and reduced positive marital quality (Helms et al 2014;Robila and Krishnakumar 2005). Moreover, couples' residence time in the U.S. is one of the indicators of immigrants' processes of ''Americanization''.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MARITAL SATISFACTION AND WELL-BEING Satisfaction with marriage has been shown to be influenced by multiple, often interacting variables, with roots in premarital cognitions and behaviors (Johnson & Anderson, 2013). These wide-ranging predictors of marital satisfaction include dyadic coping strategies (Landis, Peter-Wright, Martin, & Bodenmann, 2013); family-of-origin influence (Peltz Dennison, Silverberg Koerner, & Segrin, 2014); personality similarities and differences (O'Rourke, Claxton, Chou, Smith, & Hadjistavropoulos, 2011); role balance (Chen & Li, 2012); workload and job satisfaction (van Steenbergen, Kluwer, & Karney, 2011); economic pressure, cultural adaptation stress, depression (Helms, Supple, Jinni, Rodriguez, Cavanaugh, & Hengstebeck, 2014); physical attractiveness of partner (Meltzer, McNulty, Jackson, & Karney, 2014); love attachment style (Ottu & Akpan, 2011); parenthood (Twenge, Campbell, & Foster, 2003); and characteristics of children (Mohammadi et al, 2012).…”
Section: Please Scroll Down For Articlementioning
confidence: 98%
“…The negative role economic stress plays in the quality of individual, marital, and family well-being is well established (Fonseca, Cunha, Crespo, & Relvas, 2016;Helms et al, 2014;Zurlo, Yoon, & Kim, 2014). Economic stress is associated with feelings of scarcity or threat due to uncertainty or inability to meet basic needs, to satisfy wants and luxuries, and to provide security, flexibility in choices, and a safety net.…”
Section: Introductionmentioning
confidence: 99%